Creating knowledge base of expert system with ontology use - Proskurka, Yevhen (My University, 2013)
Creating knowledge base of expert system with ontology use is considered.
Keywords: expert system; ontology; precedent; експертна система; онтологія; прецедент; экспертная система; онтология; кафедра автоматизації та комп'ютерних технологій систем управління ім. проф. А.П. Ладанюка